ETNOGRAFI KOMUNIKASI DALAM ADAT PERKAWINAN ANTAR SUKU - Hastika Indriyana; Sapta Sari; Antonio Imanda (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
This Study aimed to determine the etnography of communication in marriage between Javanese ethnic and Lembaknese ethnic. Informants were determined by using purposive sampling technique with the number of 13 informants. From the research, it could be seen that the communicative situation in Javanese and Lembaknese traditional wedding occurred several times, that is at the time of Lamaran (marriage proposal) in which male family were welcomed by the female family, Akad Nikah (Solemnization), Pijak Telur (eggs stampede) which symbolizes the beginning of family life that could produce a future generation, Sungkeman (kneeling) that is requesting prayers of both parents for the blessing, and Dahar Klimah which symbolizes that the bride and groom will live together in every situation. In addition, other communicative acts can be found from the ceremony is the giving message (advices) from the elders to the bride and groom about living in harmony in the household despite coming from different ethnics. Keywords: ethnography of communication, traditional wedding ceremony, Javanesse, Lembaknese